African Studies without Ethics Dumping: An Integrative Study of Research Ethics Governance in Burkina Faso and Kenya - Fayemi, Kazeem; Akin-Otiko, Akinmayowa (African Studies without Ethics Dumping: An Integrative Study of Research Ethics Governance in Burkina Faso, Kenya, Nigeria, and South Africa, 2021)
Report on focus group discussion completed
Keywords: Researcher; Historian; Anthropologist; Linguist; Integrative Studies; Ethics Dumping